Zionism and the quest for justice in the Holy Land - Wagner, Donald E.; Davis, Walter T. (The Lutterworth Press, 2014)
A critical examination of political Zionism, a topic o en considered taboo in the West, is long overdue. Moreover, the discussion of Christian Zionism is usually confined to Evangelical and fundamentalist settings. The present volume will break the silence currently reigning in many religious, political, and academic circles and, in so doing, will provoke and inspire a new, challenging conversation on theological and ethical issues arising from various aspects of Zionism-a conversation that is vital to the quest for a just peace in Israel and Palestine. The eleven authors offer a rich diversit.